2019
DOI: 10.21608/jes.2019.76550
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Studies on Different Nitrogen Fertilizers on Growth Yield and Volatile Oil of Thyme Plant

Abstract: To investigate the effect of different types of nitrogen fertilization the growth and productivity of thyme within reducing the harm effects of the excess of nitrogen fertilizers as an environmental and healthy problems, two successive experiments were carried out in pots during 2016, 2017 season's at the experimental green house Faculty of Agriculture, Ain Shams University Cairo , Egypt. Three types of nitrogen fertilizers amonium nitrate, ammonium sulphate and Urea, with three concentrations (40%, 60%, 80%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…The data in Table 4 and figure 1 also revealed that under the same rate of bio treatment (T. viride, ver micompost or Amf) treating the plants with different nitrogen forms resulted in significant increase in veg etative growth parameters compared to control and among the tested nitrogen forms, with the applica tion of ammonium sulfate leading to superior growth compared with ammonium nitrate or urea. The increases in vegetative growth parameters due to ammonium sulfate treatments are in agreement with the findings of several studies on different plants including Cynara cardunculus (Sarhan et al, 2014), Urtica pilulifera (Wahba et al, 2014), Nigella sativa (Khalid and Shedeed, 2015), Sunflower (El Mantawy, 2017;El Sayed, 2020), Thymus vulgaris (Basal et al, 2019) and Jojoba (Hegab et al, 2021).…”
Section: Vegetative Growth Parameterssupporting
confidence: 89%
“…The data in Table 4 and figure 1 also revealed that under the same rate of bio treatment (T. viride, ver micompost or Amf) treating the plants with different nitrogen forms resulted in significant increase in veg etative growth parameters compared to control and among the tested nitrogen forms, with the applica tion of ammonium sulfate leading to superior growth compared with ammonium nitrate or urea. The increases in vegetative growth parameters due to ammonium sulfate treatments are in agreement with the findings of several studies on different plants including Cynara cardunculus (Sarhan et al, 2014), Urtica pilulifera (Wahba et al, 2014), Nigella sativa (Khalid and Shedeed, 2015), Sunflower (El Mantawy, 2017;El Sayed, 2020), Thymus vulgaris (Basal et al, 2019) and Jojoba (Hegab et al, 2021).…”
Section: Vegetative Growth Parameterssupporting
confidence: 89%